Safety of vitamin K antagonist treatment for splanchnic vein thrombosis: a multicenter cohort study. (13th May 2015) - Riva, N.; Ageno, W.; Poli, D.; Testa, S.; Rupoli, S.; Santoro, R.; Lerede, T.; Piana, A.; Carpenedo, M.; Nicolini, A.; Ferrini, P. M.; Tosetto, A.; et al.
Summary Background The treatment of splanchnic vein thrombosis (SVT) is challenging, due to the increased risk of bleeding and potentially life‐threatening complications. Current recommendations are based on evidence from the treatment of venous thrombosis in usual sites, but small observational studies in SVT population suggest that the bleeding risk may offset the benefit of anticoagulant treatment in this setting. The aim of this study was to evaluate the safety of vitamin K antagonists (VKAs) in SVT patients. Methods We retrospectively included SVT patients treated with VKAs followed by 37 Italian anticoagulation clinics, until June 2013. The primary outcome was the incidence of major bleeding (MB), according to the ISTH definition, during VKA treatment. Vascular events, including both arterial and venous thrombosis, and mortality were also documented. Results Three hundred and seventy‐five patients were included (median age 53 years; 54.7% males). During a median VKA treatment duration of 1.98 years, 15 MB events occurred, corresponding to an incidence rate of 1.24 (95% confidence interval [CI], 0.75–2.06) per 100 patient‐years. Gastrointestinal bleeding represented 40% of all MB events. At multivariate analysis, the presence of esophageal varices emerged as independent predictor of MB (hazard ratio 5.4; 95% CI, 1.4–21.1). The incidence rate of vascular events on treatment was 1.37 (95% CI, 0.84–2.23) per 100 patient‐years and the mortality rate was 0.83 (95% CI, 0.44–1.54) per 100 patient‐years. Conclusions Selected SVT patients followed by anticoagulation clinics for the management of VKA treatment show a low rate of major bleeding and vascular events.